A needs analysis of ethnomathematics based digital learning modules: teachers and students perceived usefulness in senior high school mathematics - Bela, Maria Editha; Tali Wangge, Maria Carmelita; Wewe, Melkior; Hari, Christina Lusiana; Sayangan, Yohanes Vianey; Pantaleon, Kristianus Viktor; Kila Keli, Yohanes Oskarito (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to analyze the instructional needs and perceived usefulness of ethnomathematics-based learning modules in senior high school mathematics. The focus is placed on curriculum alignment, integration of local cultural contexts, and the potential of these modules to support contextual and meaningful learning experiences for both teachers and students. Method: A descriptive mixed-methods design was employed, combining quantitative and qualitative approaches. The participants consisted of four mathematics teachers and twenty students drawn from four senior high schools in the Golewa region. Data were collected using closed-ended questionnaires based on a four point Likert scale to capture perceptions related to instructional needs, relevance, and usefulness of ethnomathematics based modules. To enrich and validate the quantitative data, semi-structured interviews were conducted with selected participants. Quantitative data were analyzed using percentage-based Likert index calculations, while qualitative data were analyzed descriptively to support interpretation of the findings. Findings: The results indicate that the availability of ethnomathematics-based teaching modules in senior high school mathematics remains limited. From the teachers’ perspective, the average needs score reached 85.5%, highlighting strong demands for contextual learning resources aligned with the curriculum and local culture. From the students’ perspective, the perceived usefulness score averaged 82%, indicating positive responses toward increased engagement, improved conceptual understanding, and stronger connections between mathematics and everyday life. Significance: The findings demonstrate that ethnomathematics-based learning modules represent a valuable instructional innovation with the potential to enhance the quality of mathematics learning. This study provides empirical evidence to inform the development of culturally responsive and context-based learning resources that support meaningful mathematics education.